Tonalites from the Hospitais Massif (Ossa-Morena Zone, SW Iberian Massif, Portugal): II: Geochemistry and petrogenesis - Moita, P. (2005)
As described in the first part of this work (Moita et al., this volume), the Hospitais Massif belongs to a synorogenic Variscan magmatic association, intrusive in a gneissic-migmatitic complex of the Évora High-Grade Metamorphic Terrains. In this paper, geochemical data obtained on tonalites and dioritic enclaves, from the Hospitais Massif, and on gabbros, from smaller plutonic bodies in the neighbourhood of that massif, are used to constrain hypotheses on the petrogenetic processes responsible for the mentioned lithologies. Major and trace element geochemistry reveal calc-alkaline affinities and suggest that gabbros, diorites and tonalites belong to a magma suite derived dominantly by fractional crystallization. The presence of microgranular mafic enclaves, within the tonalites, could be interpreted as representing an additional process of mingling/mixing for the evolution of these rocks. According to their geochemical features, the enclaves may have resulted from an intermediate differentiation product internally mixed with the tonalite melt. A filter-pressing process can explain the amphibole-dominated cumulate REE pattern displayed by the enclaves.